Enterocyte Beta Amyloid-Lipoprotein Homeostasis: Implications for Alzheimer's Disease Risk - Galloway, Susan (Curtin University, 2015)
Alzheimer’s disease beta-amyloid (Aβ) was found in small intestinal enterocytes in association with chylomicrons in wild-type mice. The expression of Aβ was regulated by the availability of substrate from the diet; fasting abolished Aβ, whilst low-fat feeding attenuated Aβ compared to high-fat feeding. This thesis provides novel point of view in context of dietary fat and in particular saturated fatty acids in modulating AD risk.